The effectiveness of group guidance in increasing the students assertiveness on prevent drug abuse - Berru Amalianita; Firman Firman (Jurnal Aplikasi IPTEK Indonesia, 2019)
Drug abuse in the form of increased aseertiveness through group guidance services in efforts to prevent drugs is rarely done is schools. This study aims to see the effectiveness of guidance services group in increasing student assertiveness to prevent drug abuse. This study used quantitative research with experimental methods Quasi Experiment Design approach through the design of the Non Equivalent Control Group Population research students of SMK Negeri 1 Sumatera Barat and research samples of class XI Mekatronika and XI Audio Visual. Data collected by questionnaire and analyzed using Wilxocon Signed Rank Test and Kolmogorov Smirnov Two Independent. Based on the results of the study it was found that group guidance services were effective in increasing student assertiveness to prevent drug abuse.